Relokasi Permukikan Warga Dukuh Semonet Akibat Banjir Pasang Surut Air Laut (Rob) - M Arif Wibowo (Bapperida Kabupaten Pekalongan, 2023)
Tidal flooding (ROB) has become a serious threat to residential areas in Dukuh Semonet. Periodic ROB flooding causes material losses, damages infrastructure, and threatens the safety of residents. Therefore, settlement relocation is a proposed solution to overcome this problem. This abstract describes a study of residential relocation of Dukuh Simonet residents due to ROB flooding. The study was conducted to analyze the conditions of the affected settlements, understand the challenges and opportunities, and formulate an effective relocation strategy. Through analysis of field data and interviews with local residents, the conditions of settlements affected by ROB flooding were revealed. The level of significant damage to buildings and infrastructure, as well as threats to the health and lives of residents were the main highlights. A SWOT analysis was used to evaluate the strengths, weaknesses, opportunities, and threats related to settlement relocation. Strengths and opportunities such as government support, access to resources, and public awareness of the importance of relocation were positive factors in formulating a strategy. However, challenges such as relocation financing, determining a suitable location, and coordination between stakeholders were also identified. In addition, the social and cultural aspects of the local community must be considered so that the relocation process can be well received. Based on the results of the analysis, the proposed relocation strategy involves residents in decision-making, providing basic facilities in the new location, and building adequate infrastructure. Long-term planning and post-relocation monitoring are also important parts of the strategy. This study has important implications in maintaining the sustainability of the Dukuh Semonet residents' settlements and improving the quality of life of residents. It is hoped that the results of this study can be used as a basis for developing an effective relocation plan, reducing the risk of ROB flooding, and creating a safe and sustainable environment for the residents of Dukuh Semonet.